Gut Microbiota and Environment in Coronary Artery Disease - Piccioni, Andrea (Int J Environ Res Public Health, 2021)
In recent years, studies evaluated the associations between coronary artery disease (CAD) and fecal gut microbiota composition. This opens new perspectives on therapeutic strategies to prevent CAD representing the leading cause of mortality in Western societies. We have conducted a review of the literature regarding the characteristics of the gut microbiota of CAD patients, its underlying mechanisms and their associations with pollution and the Western diet. The latest evidence confirms that an abnormal microbiota predisposes to the development of CAD and differs in composition compared to the microbiota of healthy patients; the results are, however, heterogeneous. The most studied underlying mechanisms involve the production of trimethylamine-N-oxide (TMAO), the synthesis of short-chain fatty acids (SCFAs) and the immune system activation mediated by lipopolysaccharides (LPS). Despite a large amount of available data, there is no evidence about the role of a specific type of gut microbiota in the risk of developing acute coronary syndrome (ACS). Moreover, no relationship has been assessed between the gut microbiota and the characteristics of coronary plaques in humans. However, a close association has been found between both pollution and the Western diet and gut microbiota and CAD. Further studies are needed to clarify the associations between gut microbiota, CAD, and ACS to find efficient therapeutic strategies.